Perlindungan Hukum bagi Montir di Bengkel Fallen Motor Situbondo Perspektif Undang-Undang Ketenagakerjaan dan Hukum Islam - Muhammad Najib Amrullah; Sutrisno RS (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
Human life is inseparable from law, law has an important role in the effort to create conditions that enable humans to feel safe, peaceful, and their rights and existence are protected. Law Number 13 of 2003 concerning Manpower regulates legal protection for workers that must be fulfilled by employers as well as in Islamic law which also requires the fulfilment of rights to workers following what has been done. Likewise in the automotive business world, employers are obliged to protect their workers. However, the Fallen Motor Workshop in Besuki sub-district, Situbondo district, in the implementation of its business, neglects the rights of its workers a little. The purpose of this study is to determine the legal protection regulations for mechanics according to Law Number 13 of 2003 concerning Manpower and its implementation of legal protection for mechanics at the Fallen Motor Workshop, Besuki sub-district, Situbondo district according to the Manpower Act and Islamic Law. This research is a type of qualitative research using a case approach.